Vertical gastric plication versus Nissen fundoplication in the treatment of gastroesophageal reflux in children with cerebral palsy - Antonio Paulo Durante; Sergio Tomaz Schettini; Djalma José Fagundes (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Association between neurological lesions and gastroesophageal reflux disease (GERD) in children is very common. When surgical treatment is indicated, the consensus favors the fundoplication technique recommended by Nissen, despite its high morbidity and relapse rates. Vertical gastric plication is a procedure that may have advantages over Nissen fundoplication, since it is less aggressive and more adequately meets anatomical principles. The authors proposed to compare the results from the Nissen and vertical gastric plication techniques. DESIGN AND SETTING: Randomized prospective study within the Postgraduate Surgery and Experimentation Program of Unifesp-EPM, at Hospital do Servidor Público Estadual (IAMSPE) and Hospital Municipal Infantil Menino Jesus. METHODS: Fourteen consecutive children with cerebral palsy attended between November 2003 and July 2004 were randomized into two groups for surgical treatment of GERD: NF, Nissen fundoplication (n = 7); and VGP, vertical gastric plication (n = 7). These were clinically assessed by scoring for signs and symptoms, evaluation of esophageal pH measurements, duration of the operation, intra and postoperative complications, mortality and length of hospital stay. RESULTS: The mean follow-up was 5.2 months; symptoms were reduced by 42.8% (NF) (p = 0.001) and 57.1% (VGP) (p = 0.006). The Boix-Ochoa score was favorable for both groups: NF (p < 0.001) and VGP (p < 0.042). The overall mortality was 14.28% in both groups and was due to causes unrelated to the surgical treatment. CONCLUSION: The two operative procedures were shown to be efficient and efficacious for the treatment of GERD in neuropathic patients, over the study period.